BIOENERGETSKI KRITERIJUMI IZDRŽLJIVOSTI SPORTISTA - Nikolaj Volkov; Duško Bjelica; Grujica Radunović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2005)
Human endurance under conditions of heavy muscle activity are determined, primarily, upon changes which occur in the sphere of bioenergetic change. Depending on the dominant source of energy, there are three basic components of endurance: - alaktatic anaerobic - glycolitic anaerobic - aerobic Each of these components can be numerically graded by three types of criteria: - strength criteria - volume criteria - criteria of effectiveness Concrete manifestations of endurance of athletes always have a specific character and that manifestation of endurance is determined at the level of bioenergetic potentials being made in the training process in a specific kind of exercise. This paper touches upon a very important issue in sports, that of endurance, with particular attention paid to engometrical and bioenergetical criteria for exact measurement of such endurance in top athletes.